THE ISLAMIC CHARACTER VALUES OF KUPATAN TRADITION IN BANGKALAN, MADURA, EAST JAVA - Tutuk Ningsih (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
Characters are formed in a community through tradition, custom, and cultural activities. A religious tradition called Kupatan has been car- ried out by the Madurese community, especially in Bangkalan, and has been passed down from generation to generation. This study aims to determine the Islamic character values in the Kupatan tradition. The re- sults of this study reveal that the Kupatan tradition could build Islamic character values of the Bangkalan community through various activities in it, namely silaturrahmi, anjang-sana, and almsgiving. The Kupatan tradition is held every year in the month of Shawwal, to be precise after seven days of the Sunnah fast by following the instructions of their an- cestors. Through this tradition, people could increase friendships (main- taining kinship ties) through visits to the houses of family, friends, and fellow community members (silaturrahmi). Silaturrahmi is highly recom- mended in Islam since it could extend life and expand sustenance (rezeki). Besides, the tradition of almsgiving (sedekah), in which all members of the community, both the fortunate and the less fortunate ones, exchange gifts, could also build moral values. The gift-givers should not expect anything in return but the pleasure (ridha) of Allah SWT. The manifesta- tion of Islamic character values in Kupatan could form a community that is religious, responsible, socially and environmentally caring, friendly and communicative, loves the homeland, and is creative.